DEVELOPING READING MATERIALS OF PROCEDURE TEXTS FOR SECOND GRADE STUDENTS OF BEAUTY PROGRAM AT SMK NEGERI 8 MEDAN - Cory Flora Oktavia Butarbutar; Willem Saragih; Muhammad Natsir (Universitas Negeri Medan, 2018)
The objective of this study is to develop suitable procedure text materials for reading skill, for Beauty program students. It was found that procedure text materials provided in the students’ textbook were not suitable to the needs and interests of Beauty program students. This research was conducted based on educational research and development (R&D) through six steps, namely: gathering data, analyzing data, developing procedure text materials, validating procedure text materials, revising procedure text materials and final product. There are some instruments that were applied in this research namely questionnaire and interview .The subject of this study was XI Grade of Beauty program. Based on the needs analysis conducted there were 4 procedure texts related to Beauty program developed. The researcher developed the text by selecting and adapting relevant procedure texts related to Beauty program from internet and book as the sources. Then, the selected texts were adapted based on the principles of materials development in order to present well organized suitable procedure text materials. These developed procedure text materials had been validated by two experts and the average score gotten is 4.07. It is categorized “Good” since the mean is within the interval 3.40 < ≤ 4.19. It means that the developed procedure text materials for reading skill are suitable for the eleventh grade students of Beauty program. Key words: research and development (R&D), procedure text, Beauty program